Feasibility Of Augmented Reality-Based E-Modules On Seam Material To Increase Vocational Students' Interest In Learning - Muzdalifah, Alfina; Wahyuningsih, Sri Endah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
In the context of vocational education, learning emphasizes the mastery of practical skills that align with workforce demands. In the Basic Sewing Techniques subject, particularly the subtopic of seam types, students still face difficulties in understanding seam characteristics and their proper application when learning relies mainly on textbooks and conventional teaching methods. This condition shows that there is a need for new and engaging learning tools that can make educational content easier to understand. This study aims to create an e-module that uses Augmented Reality (AR) to assist in learning the Basic Sewing Techniques subject on seam types and to analyze its feasibility as a learning medium for vocational high school students. The study used a Research and Development (R&D) method based on the ADDIE model, which has five steps: analyzing, designing, building, putting into action, and assessing. Information was gathered through interviews, observing lessons, reviewing expert feedback forms, and collecting student opinions. These data came from subject matter experts, media specialists, teachers, and students who are part of the Fashion Design program. The results indicate that the developed AR-based e-module is categorized as very feasible, with validation scores of 94.84% from subject matter experts and 97.37% from media experts. Practicality testing shows that the e-module is highly practical, achieving a score of 96.95%. Furthermore, students' learning interest is classified as high, with improvement scores of 0.71 based on student questionnaires and 0.80 based on teacher observations. Keywords: E-module, Augmented Reality, Basic Sewing Techniques, Vocational School Students